Instilling Islamic Character Education Values ??in Street Children at the Al-Falah aL-Makky Islamic Boarding School in Gondanglegi Malang - Yazidul Busthomi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
The purpose of the study is to describe, analyze and provide interpretation of the instillation of Islamic character education values ??in street children at the Al-Falah Al-Makky Islamic Boarding School, Putat Lor, Gondanglegi, Malang. This study uses a qualitative approach, a type of research that produces findings that are not obtained by statistical procedures or other quantification tools. This can lead to research on a person's life, history, behavior or interactional relationships. This concept emphasizes that qualitative research is characterized by an emphasis on the use of non-statistics (mathematics), especially in the process of data analysis to produce research findings naturally.